2015
DOI: 10.4103/2008-7802.165157
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality and treatment completion of tuberculosis patients in Isfahan Province from 2006 to 2011

Abstract: Background:Regarding cases of infectious diseases tuberculosis (TB) is the most important cause of death and according to the DALY criteria, this disease has the seventh position in global disease ranking. In this study, we aim to determine the risk factors, which have a significant effect on the treatment completion and mortality of TB patients.Methods:This study is a retrospective cohort study. The sample is made up of registered TB patients in the Isfahan Province from 2006 to 2011. Information of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…Mortality shows significant relation with increasing age, poverty, anemia, CLD, DM, HIV, HTN, recurrent TB, and smoking. Similar to our result different studies show the significance of various risk factors and mortality 18,21,22. A Pakistani study by Khaliq A et al on different social and environmental risk factors in PTB patients reported the significant relation of PTB mortality with male gender, poverty, smoking, DM, asthma, HIV, and reoccurrence of TB 21.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Mortality shows significant relation with increasing age, poverty, anemia, CLD, DM, HIV, HTN, recurrent TB, and smoking. Similar to our result different studies show the significance of various risk factors and mortality 18,21,22. A Pakistani study by Khaliq A et al on different social and environmental risk factors in PTB patients reported the significant relation of PTB mortality with male gender, poverty, smoking, DM, asthma, HIV, and reoccurrence of TB 21.…”
Section: Discussionsupporting
confidence: 91%
“…First important finding of current study was the higher rate of mortality in PTB patients i.e., 13.5%, whereas most of the other studies reported the lower mortality prevalence than current study such as Asgedom SW et al, 11.3%,17 Shahrezaei M et al, 1.6%,18 and Rodrigo T et al, 3.5% 19. Another study by Takarinda KC et al reported the higher prevalence of mortality 22.0% in TB patients 20.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…[ 7 ] Enolase-2 (ENO-2) is the phosphopyruvate hydratase enzyme of glycolysis of neuron origin; hence, it is also known as ENO-γ or the neuron-specific enolase (NSE). [ 8 9 ] ENO-2 is found in various tissues including the brain, macrophages, neuroendocrine cells, neuroendocrine cells tumors, such as the small cell lung cancer,[ 10 11 ] active PTB,[ 12 ] and poor neurological outcome in cardiac arrest patients. [ 13 ] The high-sensitivity C-reactive protein (hs-CRP) is an acute phase protein biomarker for inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%